PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA MENGGUNAKAN METODE BELAJAR AKTIF TIPE LEARNING TOURNAMENT DAN CONTRACT LEARNING SISWA KELAS X MAN KAJAI KABUPATENPASAMAN BARAT - Melia Roza (STKIP Pesisir Selatan, 2016)
This research is motivated by the results obtained studying mathematics students is still low. This study aims to determine whether there are differences between the results of learning math using active learning methods Tournament type Learning and Learning Contract type class X MAN Kajai West Pasaman. This type of research is an experimental research. The population in this study were students of class X MAN Kajai West Pasaman Academic Year 2010-2011. The sampling technique is done randomly selected as a sample class is a class X.A as an experimental class I and class II X.B as an experimental class. The instrument used in this study is the achievement test. The test form used is the form of an essay by the reliability of the test is r_11 = 0.69. Data analysis technique used is test two parties at α = 0.05 with the help of MINITAB software. Based on the results of data analysis known that both classes of normally distributed and homogeneous samples. The results of the hypothesis test obtained P-Value equal to 0,031 means smaller than α = 0.05, then the hypothesis in this study received. It can be concluded that there are differences in mathematics learning outcomes of students who use active learning methods Tournament type Learning and Learning Contract Class X MAN Kajai West Pasaman.